EDUKASI PENERAPAN PROTOKOL KESEHATAN DI ERA PANDEMI COVID-19 PADA DESA WISATA SIDOREJO INDAH (DEWISRI) - Ani Sutriningsih; Wahyu Dini Metrikayanto; Vita Maryah Ardiyani (Jurnal LENTERA, 2022)
The implementation of this community service aims to provide education on the application of health protocols at the location of the Sidorejo Indah Tourism Village (DEWISRI) Sidorejo Village, Jabung District. The tourism aspect is one part affected by the COVID-19 pandemic. In tourism operations in the pandemic era, it is necessary to implement health protocols as an effort to prevent and control the spread of the COVID-19 outbreak. DEWISRI tourist village, Sidorejo Village, Jabung District, Malang Regency is one of the tourist attractions affected by the COVID-19 pandemic. The purpose of community service activities is to provide education to increase knowledge about health protocols in the pandemic era. The targets in this activity consist of managers, DEWISRI employees, and food and beverage sellers around tourist sites as many as 10 people. The method of implementing community service activities is carried out in three stages, namely first measuring public knowledge about health protocols (pre test) using a questionnaire, second providing education about health protocols, and third measuring community knowledge about health protocols (post test) using questionnaires. The results of the univariate analysis showed that more than half of the participants (80%) had knowledge in the low category and after being given education about health protocols, it was found that more than half of the participants (70%) had sufficient knowledge. Education on the application of health protocols has a direct impact, namely increasing knowledge about health protocols in the community.